Pharmacokinetics and Pharmacodynamics of Melagatran, a Novel Synthetic LMW Thrombin Inhibitor, in Patients with Acute DVT - Eriksson, H.; Eriksson, U. G.; Frison, L.; Hansson, P. O.; Held, P.; Holmström, M.; Hägg, A.; Jonsson, T.; Lapidus, L.; Leijd, B.; Stockelberg, D.; Säfwenberg, U.; Taghavi, A.; Thorsén, M. (Thrombosis and Haemostasis, 1999)
Forty-eight patients with acute proximal deep vein thrombosis (DVT) were randomised to intravenous infusions for 4 to 6 days with melagatran, a novel synthetic low molecular weight thrombin inhibitor, or unfractionated heparin adjusted by the activated partial thromboplastin time (APTT). The aim of the study was to investigate the pharmacokinetics, pharmacodynamics and the safety of melagatran therapy at three different doses. Steady-state plasma concentrations were rapidly achieved and maintained throughout the infusion period. The mean plasma concentrations in the low, medium and high dose groups were 0.17, 0.31 and 0.53 μmol/l, respectively. The prolongation of APTT was stable during the melagatran infusions and correlated to the plasma concentration. Phlebographically verified regression of thrombus size measured as decrease in Marder score was seen after 4 to 6 days in 8 of 12 patients, 6 of 12 patients and 5 of 11 patients in the low, medium and high dose groups of melagatran and in 5 of the heparin-treated patients. In the low dose group with melagatran, thrombus extension was seen in one patient. At the dose levels studied, melagatran was well tolerated with no clinically significant bleeding problems, suggesting that melagatran could safely be given to patients suffering from DVT.